Asphaltenes : chemical transformation during hydroprocessing of heavy oils - Ancheyta, Jorge (CRC Press/Taylor & Francis, 2009)
During the upgrading of heavy petroleum, asphaltene is the most problematic impurity since it is the main cause of catalyst deactivation and sediments formation. Exploring many aspects related to asphaltenes composition and conversion, Asphaltenes: Chemical Transformation during Hydroprocessing of Heavy Oils highlights the various changes that these heavy and complex molecules undergo during catalytic hydroprocessing. After defining and characterizing asphaltene structure, the book examines the composition of petroleum and the processes and catalysts for upgra.
Keywords: Petroleum -- Refining.; Heavy oil.; Hydrogenation.; Hydrocracking.; elektronické knihy; electronic books